2012
DOI: 10.1159/000341611
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequence and Analysis of EhV-99B1, a New Coccolithovirus from the Norwegian Fjords

Abstract: Coccolithoviruses are giant dsDNA viruses that infect Emiliania huxleyi, the most ubiquitous marine microalga. Here, we present the genome of the latest coccolithovirus strain to be sequenced, EhV-99B1, and compare it with two other coccolithovirus genomes (EhV-86 and EhV-163). EhV-99B1 shares a pairwise nucleotide identity of 98% with EhV-163 (the two strains were isolated from the same Norwegian fjord but in different years), and just 96.5% with EhV-86 (isolated in the same spring as EhV-99B1 but in the Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Similarly, Pagarete et al [44] report differences in the type of tRNAs encoded by EhV-86 and EhV-99B1. However, after an in-depth study of the different codon frequencies of the genomes of EhV-86 and EhV-99B1, they concluded that the difference in tRNAs does not correspond to the respective codon frequencies in each genome and that it is more likely that strain-specific tRNA differences represent adaptations to different host strains.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Similarly, Pagarete et al [44] report differences in the type of tRNAs encoded by EhV-86 and EhV-99B1. However, after an in-depth study of the different codon frequencies of the genomes of EhV-86 and EhV-99B1, they concluded that the difference in tRNAs does not correspond to the respective codon frequencies in each genome and that it is more likely that strain-specific tRNA differences represent adaptations to different host strains.…”
Section: Resultsmentioning
confidence: 96%
“…This transporter is encoded by all EhV isolates from the English Channel and the Scottish coast, but absent in the Norwegian isolate EhV-99B1 ([44]; and this study) and the partially sequenced genome of the Norwegian isolate EhV-163 (not included in this study) [43]. Instead, a 75-bp scar remnant of the transporter gene is still present at the 3′ end of this gene in both Norwegian isolates, and is replaced by a putative endonuclease [43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations